The Effect of Job Satisfaction and Physical Work Environment on Teacher Performance of SMK Angkasa Lanud Husein Sastranegara Bandung - Nurfaijah, Putri Dilla; Gumilar, Dedi (Dinasti Publisher, 2024)
The purpose of this study was to determine the effect of Job Satisfaction and Physical Work Environment on the performance of teachers in SMK Angkasa Lanud Husein Sastranegara Bandung both partially and simultaneously. The population in this study is teachers at SMK Angkasa Lanud Husein Sastranegara Bandung, a total is 43 teachers. The sampling technique used in this study is saturated sampling technique. The method used in this study is Quantitative Methods with data collection using interview techniques, questionnaires, observations, library studies and the researchers documentation concluded that: 1) work packages have significant effects on Teacher’s performance; 2) The physical working environment has a significant effect on the Teacher’s performance. In simultaneous testing, Job Satisfaction and physical work environment have a positive and significant effect on the performance of teachers in SMK Angkasa Lanud Husein Sastranegara Bandung. The magnitude of the effect of Job Satisfaction and physical work environment is shown with the Adjustable R-Square score of 66.7% and the remaining 33.3% are influenced by other variables not studied in the study.